大气对星载盐度计辐射传输特性及盐度反演的影响研究 - Wang, Yingqiang; Yan, Wei; Wang, Yeying; Han, Yueqi (Beijing da xue xue bao, 2018)
Using the MPM93 model, the L-band of atmospheric radiation parameters and salinity meter observation brightness temperature under different weather conditions are numerically simulated based on the microwave radiation transfer equation, and using the maximum likelihood estimation algorithm to the inversion of sea surface salinity, which research the influence of different weather conditions on the sea surface salinity retrieval value. The simulation results show that the atmospheric radiation parameters of cloud, fog and haze which considered the effects of suspended droplets are almost the same as those in clear sky, and the influence of them can be neglected. However, the influence of rainfall on atmospheric radiation parameters can't be neglected, and the error of salinity retrieval increases obviously with the increase of rainfall rate. When the rainfall rate is fixed, the salinity inversion error decreases with the increase of sea surface temperature, and the salinity retrieval error is smaller under low